The Influence of Organizational Culture, Work Competence, and Career Development on Employee Productivity of PT Zona Karya Mendunia in Sukoharjo - Fahmi, Shoahudin; Sundjoto; Rahayu, Sri (JURNAL AKUNTANSI DAN MANAJEMEN, 2024)
Employee productivity plays an important role in the company, in order to continue to increase, the human resources owned must have a good organizational culture, adequate competence, and continue to develop themselves to be highly competitive. This study examines the influence of organizational culture, work competence, and career development on the productivity of PT. Zona Karya Mendunia is worldwide both partially and simultaneously. The population in this study amounted to 55 people. Data collection techniques use questionnaire instruments that have been tested for validity, reliability, normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests. The analysis tool used is multiple linear regression. Based on the results of the analysis showed that partially the organizational culture variable obtained a calculated t value of 5.241 greater than t table 2.007, so that H0 was rejected and H1 was accepted. The variable work competence obtained t count 1.113 smaller than t table 2.007. so H0 is accepted and H1 is rejected. The career development variable obtained a calculated t value of 1.093 smaller than t table 2.007, so that H0 was accepted and H1 was rejected. While in the simultaneous F test, the variables of organizational culture, work competence, and career development on employee productivity obtained a calculated F value of 56.296 and a significance value of 0.000 which turned out to be smaller than the degree of freedom used which was 0.05 (0.000 < 0.05), so that H0 was rejected and H1 was accepted. The conclusion of this study shows that organizational culture partially has a positive effect on employee productivity, while work competence and career development partially have no effect on the productivity of PT. Zona Karya Mendunia employees. Worldwide Work Zone in Sukoharjo. As for the results of research consisting of organizational culture, work competence, and career development together (simultaneously) have a significant effect on employee productivity at PT. Zona Karya Mendunia in Sukoharjo.